Multiwall carbon nanotube polyvinyl alcohol-based saturable absorber in passively Q-switched fiber laser - Ahmad, H; Ismail, Mohammad Faizal; Hassan, S.N.M; Ahmad, Faizah; Zulkifli, Mohd Zamani; Harun, Sulaiman Wadi (OSA Publishing, 2014)
In this work, we demonstrated a compact Q-switched erbium-doped fiber laser capable of generating high-energy pulses using a newly developed multiwall carbon nanotube (CNT) polyvinyl alcohol (PVA) thin film based saturable absorber. Q-switched pulse operation is obtained by sandwiching the thin film between two fiber ferrules forming a saturable absorber. A saturable absorber with 1.25 wt. % of PVA concentration shows a consistency in generating pulsed laser with a good range of tunable repetition rate, shortest pulse width, and produces a high pulse energy and peak power. The pulse train generated has a maximum repetition rate of 29.9 kHz with a corresponding pulse width of 3.49 μs as a function of maximum pump power of 32.15 mW. The maximum average output power of the Q-switched fiber laser system is 1.49 mW, which translates to a pulse energy of 49.8 nJ. The proposed method of multiwall CNT/PVA thin film fabrication is low in cost and involves uncomplicated processes.